Exploration of factors that affect the comparative effectiveness of physical and virtual manipulatives in an undergraduate laboratory - Chini, Jacquelyn J.; Madsen, Adrian M.; Gire, Elizabeth; Rebello, N. Sanjay; Puntambekar, Sadhana (My University, 2012)
Recent research results have failed to support the conventionally held belief that students learn physics best from hands-on experiences with physical equipment. Rather, studies have found that students who perform similar experiments with computer simulations perform as well or better on measures of conceptual understanding than their peers who used physical equipment. In this study, we explored how university-level nonscience majors’ understanding of the physics concepts related to pulleys was supported by experimentation with real pulleys and a computer simulation of pulleys.We report that when students use one type of manipulative (physical or virtual), the comparison is influenced both by the concept studied and the timing of the post-test. Students performed similarly on questions related to force and mechanical advantage regardless of the type of equipment used. On the other hand, students who used the computer simulation performed better on questions related to work immediately after completing the activities; however, the two groups performed similarly on the work questions on a test given one week later. Additionally, both sequences of experimentation (physical-virtual and virtual-physical) equally supported students’ understanding of all of the concepts. These results suggest that both the concept learned and the stability of learning gains should continue to be explored to improve educators’ ability to select the best learning experience for a given topic.
Keywords: Undergraduate physics laboratory; Virtual manipulative; Physical manipulative; Pulleys